Comparison of the antimicrobial activity of three different concentrations of aqueous ozone on Pseudomonas aeruginosa, Staphylococcus aureus, and Enterococcus faecalis – in vitro study (Ozone Therapy Global Journal, 2014)
The root canal treatment has been dramatically changed since the emergence of ozonetherapy.Due toits potent antimicrobial activity and biocompatibility, ozone can be applied as anagent to improve decontamination procedures and possibly increase success rates. The aimof this study was to compare the antimicrobial activity of 3different concentrations of aqueousozone on Pseudomonas aeruginosa, Staphylococcus aureus, and Enterococcus faecalis.Thisstudy used a standardized suspension of 3 bacteria. These suspensions were cultivated andspectrophotometrically adjusted to a final concentration of 4.46X108 CFU/mL.Then they weresubmitted to groups: Group I – aqueous ozone 2 μg/mL; Group II – aqueous ozone 5 μg/mL;Group III – aqueous ozone 8 μg/mL, and Group Control – bidistilled cold sterile water with noozone. Bidistilled cold sterile water was ozonated for 5 minutes. Then 10 mL of each suspensionwere added to 90 mL of each group in a glass flask. After 1 minute of contact, 1 mL of eachflask was added to 9 mL of 0.1% sodium tiossulfate to neutralize the ozone, and then serialdilution was performed. After 24 hours of incubation, the CFU counting was performed. Inparallel, 1 mL of each glass flask was added to 9 mL of TSB broth and incubated for 7 days forvisual analyses of turbidity broth. The results showed Group I presented Enterococcus faecalisgrowth. Group II and III presented no CFU counting, but aqueous ozone at 5 μg/mL presented2 bleary tubes of Enterococcus faecalis, indicating bacterium growth. Group III (aqueous ozone8 μg/mL) showed no CFU counting or blurry broth. According to the applied methodology, itwas possible to conclude that the aqueous ozone in concentration of 8 μg/mL was the mostefficient to eliminate the three evaluated bacteria.